Examining the Legal Impact of Presidential Threshold Implementation in the 2024 Presidential Election - Sugiharto, Imawan; Pratama, Erwin Aditya (Jurnal Dinamika Hukum, 2022)
Presidential threshold is the threshold of vote acquisition that must be obtained by political parties in an election to be able to nominate a presidential candidate. General elections for president and vice president are submitted by political parties or a combination of political parties that have at least 20% of the seats in the DPR or 25% of the national valid votes in legislative elections. The type of research used is library research. The approach used is a normative approach. The data collection technique is through literature study. And analyzed by qualitative data analysis method. The presidential threshold setting as determined by the Constitutional Court through decision Number 53/PUU-XV/2017 states Article 222 of Law Number 7 of 2017 concerning Elections which regulates the Presidential threshold requirements have an impact on political parties, due to restrictions on the constitutional rights of political parties that has a small number of seats in the DPR. Then the high threshold number will cause only political parties to nominate their president and vice president so that the implementation of the Presidential threshold is more likely to benefit the authorities and harm the people and negate the people's right to be able to choose alternative figures in the 2024 Presidential Election.Keywords: Presidential Threshold, Presidential Election, 2024 Presidential Election, President.